Getting ahead by spending more? Local community response to state merit aid programs - Rajashri Chakrabarti; Nicole Gorton; Joydeep Roy (Federal Reserve Bank of New York, 2018)
In more than half of U.S. states over the past two decades, the implementation of merit aid programs has dramatically reduced net tuition expenses for college-bound students who attend in-state colleges. Although the intention of these programs was to improve access to enrollment for high-achieving students, it is possible that they had unanticipated effects. We analyze whether state funding for higher education and K-12 education changed as a result of program implementation, and whether local school districts attempt to counter any such changes. We employ two methodologies to study whether this has been the case: a difference-in-differences model and a synthetic control estimation strategy. We find robust evidence that implementation of state merit aid programs led to an economically (and statistically) significant decline in state funding for K-12 education, which was mostly offset through increases in local revenues by school districts. These results have important implications for understanding how merit aid policies could have unintended consequences for the students they aim to support.
Keywords: H4; I2; J00; 330; merit aid; school finance; incentives